EFFECT OF PLANT DISTANCE ON THE GROWTH OF Sargassum sp. CULTURED ON BOTTOM OFF METHODS - Syarif Hidayatullah; Dewi Nur'aeni Setyowati; Nunik Cokrowati (Universitas Teuku Umar, 2021)
Spacing is one of the technical factors that affect the growth of Sargassum sp. because of its relationship with the absorption of interrelated nutrients. Differences in spacing in the cultivation of Sargassum sp. has a function to find out what distance between plants is the most appropriate so that the growth of Sargassum sp. more optimum. This is closely related to the competition of each seaweed for nutrients as food. Spacing is one of the technical factors that affect the growth of Sargassum sp. because of its relationship with the absorption of interrelated nutrients. The purpose of this study was to determine the effect of different spacing on the growth of Sargassum sp. with the basic peg method. This research was conducted in November-December 2020 in the waters of Labuhan Ijuk village, Moyo Hilir sub-district, Sumbawa Regency using an experimental method with a completely randomized design (RAL) with a maintenance period of 30 days. The results of this study showed the growth of Sargassum sp. the highest was in treatment P0 (spacing 30 cm) with an average absolute growth of 159 grams, specific growth of 3.16%, followed by P1 treatment (25 cm spacing control) with an average absolute growth of 124 grams, specific growth was 2.16% then followed by P2 treatment (20 cm spacing) with an absolute growth rate of 103 grams, specific growth averaging 2.35% and then the lowest was obtained in treatment P3 with a spacing of 15 cm with an average absolute growth value of 65 grams, specific growth 1.64% with an initial planting weight of 100 grams. Keywords: Seaweed, macro algae, aquaculture, brown algae, alginat.